Relationships Between Performance and Injury Occurrence in Athletics (Track and Field): A Pilot Study on 8 National-Level Athletes From Sprints, Jumps and Combined Events Followed During at Least Five Consecutive Seasons - Joris Chapon; Laurent Navarro; Pascal Edouard; Pascal Edouard (Frontiers in Sports and Active Living, 2022)
BackgroundPerformance success or failure in athletics (Track and Field) and the capacity to succeed are driven at the adult level, like in other sports, by many factors, injury being one of them. More information regarding the potential relationships between performance and injuries in athletics is needed.ObjectiveTo analyse the potential association between performance and occurrence of injuries in national-level athletics athletes from sprints, jumps and combined events through several seasons.MethodsWe performed a retrospective analysis of performance and injury data collected prospectively in 8 national-level athletics athletes followed during at least five consecutive seasons from 2009 to 2019. For each athlete, injuries data [total injuries (injuries) and time-loss injuries (TLI)] were collected by the same sports medicine physician throughout the study period using a medical attention injury definition. Performances during official competitions were collected on the French Federation of Athletics website, and included (i) any participation in national championships, (ii) any participation in an international competition (i.e., being national team member for an international competition), (iii) any podium at the national championships, (iv) any podium at an international competition, and (v) performance metrics normalised to the world record (WR) of the respective athletics speciality (%WR). For each athlete, we performed a descriptive analysis of the performances and injuries. We also performed four binomial logistic regressions with (1) national championships participation (yes/no) or (2) international competition participation (yes/no) as dependent variables, and injuries (yes/no) or TLI (yes/no) as independent variables, adjusted for individual athlete and number of seasons, and in models on participation in international competitions, was also adjusted for national championship participation (yes/no), with Odd Ratios (OR) with 95% confidence intervals (95%CI).ResultsAmong the 8 national-level athletics athletes included in the present study, cumulated 155 injuries, including 52 TLI (33.5%). There was an average of 2.7 ± 1.7 injuries and 0.9 ± 0.6 TLI per athlete per season over the study period. The occurrence of injuries was significantly associated with higher odds of national championships participation (OR = 4.85 [95% CI 3.10 to 3050.5], p = 0.021). The occurrence of TLI was significantly associated with higher odds of national championships participation (OR = 133.6 [95% CI 4.92 to 14251.5], p = 0.013). The occurrence of injuries or TLI were associated with insignificantly lower odds of international championships participation.ConclusionsOur present pilot study confirms that injuries are part of an athletes' life. The occurrence of at least one injury was associated with higher odds of participation in a national championship, whereas the absence of at least one injury was associated with higher odds of participation in an international championship. We hypothesised that the length of the season can play a role in the risk of injury occurrence, but if the athlete wants to reach his/her highest level, decreasing the risk of injuries seems to be of importance. Despite the caution that should be taken in the interpretation of our results, our present study confirms the interest and relevance of injury risk reduction approach in athletics.